1984
DOI: 10.1111/j.1476-5381.1984.tb10740.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo platelet aggregation in the rat: dependence on extracellular divalent cation and inhibition by nonsteroidal anti‐inflammatory drugs

Abstract: Using the Technicon Autocounter, the mechanisms involved in collagen‐induced platelet aggregation in vivo have been studied without the interference of an anticoagulant. Extracellular divalent cation was essential for in vivo platelet aggregation. Non‐steroidal anti‐inflammatory drugs completely inhibited the aggregation induced by collagen in platelet‐rich plasma in in vitro or ex vivo studies. In vivo only a maximum of 50% inhibition was achieved when release of thromboxane A2 (TXA2) was completely inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…5). As shown in previous papers indomethacin 4 mg/kg produced a 40% inhibition of collagen-induced fall in platelet count (7,13). The simultaneous injection of indometha cin 4 mg/kg and ketanserin 4 mg/kg produced a smaller fall which was not significantly different from the responses obtained with indomethacin alone.…”
Section: Collagen-induced Fall In Circulating Platelet Count In Ratssupporting
confidence: 67%
See 2 more Smart Citations
“…5). As shown in previous papers indomethacin 4 mg/kg produced a 40% inhibition of collagen-induced fall in platelet count (7,13). The simultaneous injection of indometha cin 4 mg/kg and ketanserin 4 mg/kg produced a smaller fall which was not significantly different from the responses obtained with indomethacin alone.…”
Section: Collagen-induced Fall In Circulating Platelet Count In Ratssupporting
confidence: 67%
“…5-HT may be released slowly to maintain the haemostatic and thrombogenic activity of platelets. Previous studies in this laboratory have shown that the inhibition of TxA2 by cyclooxygenase inhibitors or blocking of thromboxane recep tors with EP 045 and EP 092 only produced a 30-40% inhibition of collagen-induced aggregation (7,13,14). The question remains which aggregating agent is responsible for the 60-70% of collagen-induced aggregation in rats.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work has shown that the modified Technicon Autocounter (Smith & Freuler, 1973) can be used for studying intravascular platelet aggregation where the collagen-induced fall in platelet count can be monitored continuously without the use of an intravenous anticoagulant (Smith, 1981). When this technique was used in the rat it appeared that extracellular divalent cation is essential for normal intravascular platelet aggregation, that the endoperoxide/thromboxane pathway is responsible for part of the aggregation response and that the involvement of this pathway is dependent upon the amount of collagen exposed to the platelets (Mallarkey & Smith, 1984a).…”
Section: Introductionmentioning
confidence: 99%